Metabolic and environmental origins of volatile organic compounds in breath. Issue 11 (November 1994) - Phillips, M; Greenberg, J; Awad, J
Abstract : Although more than 200 volatile organic compounds (VOCs) have been identified in human alveolar breath, their origins are still mostly unknown. An attempt was made to determine whether the major VOCs in breath were derived from inside or outside the body–that is, were they products of metabolism or contaminants from the environment? The concentrations were measured of the 24 most abundant VOCs in the alveolar breath of 12 normal volunteers and also in the air they inspired. The polarity of the mean alveolar gradient (concentration in breath minus concentration in inspired air) was positive in 15 VOCs and negative in nine. The mean alveolar gradient varied from strongly positive (for example, 2, 3, 3-trimethylpentane), consistent with a metabolite manufactured in the body, to strongly negative (for example, isoprene), consistent with ingestion of an air pollutant which was then catabolised in vivo or excreted via an extra-pulmonary pathway.